THE IMPLICATURE OF ROALD DAHL’S CHARLIE AND THE CHOCOLATE FACTORY - Aisyah Wulandari; Fergi Cintia Amalia (Dinamika Bahasa dan Budaya, 2017)
Novel is a long prose composition, containing a series of a person’s life story with people in surrounding areas and highlight the character and nature of each offender. Sometime, the story of novel start from incident or important incident experienced by the characters, who would change they life. For example, the novel of Charlie and The Chocolate Factory, by Roald Dahl started when the charcters get a golden ticket which was very rare. In the novel there are so many conversation between characters that was usually in conversation there was a hidden meaning or meanings implied therein. This review will discuss the implicature or hidden meanings as opposed to expressed meanings in conversations taken from Roald Dahl novel, Charlie and The Chocolate Factory.Keyword: meaning of novel, implicatures, charlie and the chocolate factory